CALL DALAM PENGAJARAN BAHASA INGGRIS - Ridwan Arif Nugroho (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2011)
The use of CALL (Computer-Assisted Language Learning) in the Teaching of English as a second or foreign language is a heated discussion among language teachers and experts. Some people think that CALL is of no use in the process of teaching and learning English. Some others think that the use of CALL is unavoidable in English classes. The paper tries to discuss the advantages and disadvantages of using CALL in the teaching and learning of English.